EVALUTING THE ABILITY OF PLEUROTUS OSTREATUS AQUEOUS EXTRACT TO MODULATE GENOTOXICITY INDUCED BY CYCLOPHOSPHAMIDE IN MICE BONE MARROW CELLS - & Chechan, Farhan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to evaluate the ability of local oyster mushroom(Pleurotus ostreatus; ID: MF065715.1; cultivated until maturation in growth medium containing cumin extract) to modulate the genotoxicity induced by cyclophosphamide (CP) in bone marrow cells of mice. In vivo genotoxicity was assessed by quantifying the incidence of micronucleated polychromatic erythrocytes in the bone marrow cells of mice that were administered different doses of P.ostreatus extract (150, 200,250, and 300 mg/kg/day( respectively, individually, and in combination with CP (40 mg/kg body weight) according to the following three experimental protocols (pre 2h, post 2h, and concomitant treatment for 14 days, respectively). Analysis and microscopic examination of micronuclei (MN) revealed no mutagenic effect of P.ostreatus extract alone at all the doses evaluated. By contrast, CP administration significantly increased (P<0.05) incidence of MN. Importantly, the co-administration of P.ostreatus extract with CP caused a significant and dose-dependent reduction in MN induced by CP in the murine bone marrow cells. These data suggest that P.ostreatus extract administration has a protective effect against genotoxic damage inflicted by CP. The dietary cumin may serve as a scavenger for free radicals generated by CP and may augment the antioxidant activity of P. ostreatus extract. These findings open up new avenues for the use of oyster mushrooms in many applications, including pharmacological preparations and food supplements.